Design of a Randomized Controlled Trial of Percutaneous Posterior Tibial Nerve Stimulation for the Treatment of Refractory Fecal Incontinence in Women: The NeurOmodulaTion for Accidental Bowel Leakage Study. Issue 12 (4th December 2021) - Zyczynski, Halina M.; Arya, Lily A.; Lukacz, Emily S.; Richter, Holly E.; Rahn, David D.; Sung, Vivian W.; Visco, Anthony G.; Shaffer, Amanda; Jelovsek, J. Eric; Rogers, Rebecca; Mazloomdoost, Donna; Gantz, Marie G.; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: High-level evidence for second-line noninvasive treatments for fecal incontinence in women is limited. We present the rationale for and design of the NeuromOdulaTion for Accidental Bowel Leakage trial, a randomized controlled trial of percutaneous tibial nerve stimulation (PTNS) and validated sham stimulation in women with refractory accidental bowel leakage. Methods: The rationale and goals for a 2-part study with a run-in phase, use of a generic pulse generator for PTNS and sham stimulation, masking, participant inclusion, primary and secondary outcome measures, and adverse event collection are described. A superiority design will be used to compare change from baseline in St. Mark's score after 12 weekly stimulation sessions between PTNS and sham. Responders to initial treatment (PTNS or sham) will be assigned to scheduled or "as needed" intervention for up to 1 year. Secondary outcome measures include incontinence episodes and other bowel events recorded in a 14-day electronic bowel diary, general and condition-specific quality of life instruments, adaptive behavior, global impression of improvement, symptom control, and sexual function. Results: Sample size calculations determined that 165 participants (110 PTNS and 55 sham) would provide 90% power to detect greater than or equal to 4-point difference between PTNS and sham in change from baseline in St. Mark's score at 12 weeks. Conclusions: The methods for the NeuromOdulaTion for Accidental Bowel Leakage trial will provide high-level evidence of the effectiveness and optimal maintenance therapy schedule of a low-cost PTNS protocol in community-dwelling women seeking second-line intervention for refractory accidental bowel leakage.